2018
DOI: 10.1016/j.jaerosci.2017.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Very low particle matter mass measurements from light-duty vehicles

Abstract: Recently, there are discussions about whether current sampling and measurement practices for the regulated gravimetric PM measurement are sufficiently accurate in quantifying PM at the proposed 3 and 1 mg/mi emission standards for light-duty vehicles. In this study, a series of modifications were made to the existing gravimetric PM measurement method, aiming to preserve the integrity of the method while increasing the robustness and decreasing the testing variability. The experiments were conducted with a High… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…The two CVS PM probes (A and B) both agreed well for the FFV = 100 cm/s (within 3.8%) and FFV = 130 cm/s tests (within 2.9%) and did not show statistically significant differences. The lack of differences in averages for the CVS PM measurements suggests the single filter combined method is in good agreement with the individual filter method by phase [15]. The PFD probes showed mixed comparisons relative to the CVS_A probe.…”
Section: Pfd Comparisonsmentioning
confidence: 85%
See 3 more Smart Citations
“…The two CVS PM probes (A and B) both agreed well for the FFV = 100 cm/s (within 3.8%) and FFV = 130 cm/s tests (within 2.9%) and did not show statistically significant differences. The lack of differences in averages for the CVS PM measurements suggests the single filter combined method is in good agreement with the individual filter method by phase [15]. The PFD probes showed mixed comparisons relative to the CVS_A probe.…”
Section: Pfd Comparisonsmentioning
confidence: 85%
“…[19]. Xue et al reported greater sensitivity of gravimetric method to more aggressive US06 cycle than FTP cycle [15]. It is speculated the PM mass on this first test may have been influenced by PM desorption from the tailpipe and transfer line.…”
Section: ''mentioning
confidence: 86%
See 2 more Smart Citations
“…It is also worthwhile to evaluate the PM differences in the context of the future 2025 California LEVIII PM emissions standard of 1 mg/mi, as there is considerable interest in how effective gravimetric and other methodologies are in quantifying PM emissions at levels below 1 mg/mi (Xue et al, 2018;Sardar et al, 2015;Swanson et al, 2018). If the comparisons were based on the future 1.0 mg/mi PM standard, the average differences reduce to −2% to +26% for the AVL total PM mass measurements [StdDif_% = (NCEM-[MSS + GFM])/1.0] and to −1% to 43% for the AVL MSS soot measurements.…”
Section: Pm Emissionsmentioning
confidence: 99%